COMPARISON OF THE EFFECTS OF INTRATHECAL TRAMADOL AS AN ADJUVANT WITH BUPIVACAINE IN PATIENTS UNDERGOING INFRA-UMBILICAL SURGERIES AT TERTIARY CARE HOSPITAL, KARACHI (The Research of Medical Science Review, 2025)
OBJECTIVE: To compare the clinical outcomes of intrathecal administration of a Bupivacaine-Tramadol combination versus Bupivacaine alone in patients undergoing infra-umbilical surgeries under spinal anesthesia.METHODOLOGY: This randomized controlled trial was executed at Abbasi Shaheed Hospital in Karachi, involving 100 subjects aged between 20 and 60 years who were scheduled for elective infra-umbilical surgical procedures. The participants were systematically assigned into two distinct groups: Group A received intrathecal bupivacaine exclusively, whereas Group B was administered bupivacaine in conjunction with tramadol. The primary outcomes assessed encompassed the onset time of both sensory and motor blockade, as well as the duration of analgesia. Data were subjected to analysis utilizing SPSS version 26, with a designated significance threshold set at p<0.05.RESULTS: The mean ± SD ages of the two groups, i.e., Group A (bupivacaine alone) and Group B (tramadol-bupivacaine) were 41.82 ± 14.58 and 42.66 ± 13.72 years, respectively, and a proportion of them being males (68.0% and 74.0%). Mean sensory blockade (3.88 ± 1.69 v/s 3.10 ± 1.24; p=0.010), motor blockade (5.60 ± 1.12 v/s 5.10 ± 1.19; p=0.034) and duration of analgesia (5.38 ± 1.78 v/s 4.88 ± 1.63; p=0.147) while VAS was found as at 24 hrs (1.94 ± 0.84 v/s 1;98 ± 0.84; p=0.813).CONCLUSION: The research indicates that the administration of intrathecal tramadol as an adjunct to bupivacaine significantly enhances the rapidity of both sensory and motor blockades in individuals undergoing infra-umbilical surgical procedures. Nevertheless, it does not yield a statistically significant extension in the duration of analgesia, nor does it alleviate postoperative pain scores when compared to bupivacaine administered independently. These findings substantiate the potential application of tramadol for expedited block onset without jeopardizing safety or the efficacy of analgesia